Aryl Hydrocarbon Receptor and Kynurenine: Recent Advances in Autoimmune Disease Research - Nguyen, Nam Trung; Nakahama, Taisuke; Le, Duc Hoang; Van Son, Le; Chu, Ha Hoang; Kishimoto, Tadamitsu (Frontiers in Immunology, 2014)
Aryl hydrocarbon receptor (AHR) is thought to be a crucial factor in the regulation of immune responses. Many AHR-mediated immunoregulatory mechanisms have been discovered, and this knowledge may enhance our understanding of the molecular pathogenesis of autoimmune inflammatory syndromes such as collagen-induced arthritis, experimental autoimmune encephalomyelitis, and experimental colitis. Recent findings have elucidated the critical link between AHR and indoleamine 2,3-dioxigenase (IDO) in the development of regulatory T (Treg) cells and Th17 cells, which are key factors in a variety of human autoimmune diseases. Induction of IDO and IDO-mediated tryptophan catabolism, together with its downstream products such as kynurenine, is an important immunoregulatory mechanism underlying immunosuppression, tolerance, and immunity. Recent studies revealed that induction of IDO depends on AHR expression. This review summarizes the most current findings regarding the functions of AHR and IDO in immune cells as they relate to the pathogenesis of autoimmune diseases in response to various stimuli. We also discuss the potential link between AHR and IDO/tryptophan metabolites, and the involvement of several novel related factors (such as microRNA) in the development of autoimmune diseases. These novel factors represent potential therapeutic targets for the treatment of autoimmune disorders.